Soil profile and ground properties influence on vertical ground heat exchanger efficiency - Chwieduk, Michał; Rusowicz, Artur; Jędzrzejuk, Hanna (International Conference “Environmental Engineering”, 2017)
Soil properties have a significant impact on the performance of ground heat exchangers. Exchangers cooperating with heat pumps are a reliable and efficient source of renewable energy. In the article concentric vertical ground heat exchanger is analysed, which is a common application cooperating with heat pumps. Soil and ground properties have great importance during sizing the system, i.e.: determining the length, configuration and deployment of ground heat exchangers. With the depth the soil/ground type and its properties can change significantly. In addition, occurrence of a ground water can influence physical and thermal properties. Determination of soil type present at different depths in a specific location is possible by performing a soil profile. The article presents an analysis of the impact of two soil profiles on the efficiency of the vertical ground heat exchanger. The analysis was performed based on the model of a single heat exchanger made using CFD (Computational Fluid Dynamics) program. The model is divided into two parts: model of heat exchanger together with grout filling the borehole, second: axis-symmetric model of the ground surrounding the exchanger. Both models are coupled by first-type boundary condition. Simulations of ground heat exchanger work are made for a part of heating season period. The calculation results were compared to reference one with uniform ground profiles. Difference in heat rejected form ground in two analysed does not show high influence of ground layers on ground heat exchanger performance. On the other hand, results strongly depends on analysed soil profile.